2021
DOI: 10.25259/ijdvl_990_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of eczema among older persons: A population-based cross-sectional study

Abstract: Background: There are very few population-based studies on the prevalence of eczema among older persons Aims: To estimate the prevalence and types of eczema in those aged 65 years or more in the community and to evaluate the effectiveness of community-based interventions for case finding. Methods: In the first stage of this cross-sectional survey, trained health workers of a non-governmental organization surveyed the eligible population and identified persons likely to have eczema. In the second stage, der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The most often investigated skin condition was melanoma and/or non-melanoma skin cancer ( n = 34) [ 22 , 23 , 26 , 48 56 , 60 , 61 , 63 , 64 , 66 , 69 , 71 , 73 , 75 80 , 82 84 , 86 , 89 , 93 , 94 , 97 , 101 ], three studies did not specify ‘skin cancer’ [ 32 – 34 ]. Different types of ‘eczema’ (including atopic dermatitis) were included in eight studies [ 30 , 31 , 33 , 34 , 46 , 65 , 88 , 91 ], pressure injuries [ 45 , 68 , 81 , 85 , 90 , 99 ] and psoriasis [ 29 , 33 , 34 , 57 , 58 , 100 ] each in six studies, and xerosis/ichthyosis in five studies [ 24 , 25 , 27 , 45 , 47 , 95 ]. Other studies focused on vitiligo [ 33 , 34 , 47 , 62 ] and parasites [ 33 , 34 , 47 , 92 ], bullous pemphigoid [ 59 , 87 , 98 ], intertrigo [ 67 , 74 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most often investigated skin condition was melanoma and/or non-melanoma skin cancer ( n = 34) [ 22 , 23 , 26 , 48 56 , 60 , 61 , 63 , 64 , 66 , 69 , 71 , 73 , 75 80 , 82 84 , 86 , 89 , 93 , 94 , 97 , 101 ], three studies did not specify ‘skin cancer’ [ 32 – 34 ]. Different types of ‘eczema’ (including atopic dermatitis) were included in eight studies [ 30 , 31 , 33 , 34 , 46 , 65 , 88 , 91 ], pressure injuries [ 45 , 68 , 81 , 85 , 90 , 99 ] and psoriasis [ 29 , 33 , 34 , 57 , 58 , 100 ] each in six studies, and xerosis/ichthyosis in five studies [ 24 , 25 , 27 , 45 , 47 , 95 ]. Other studies focused on vitiligo [ 33 , 34 , 47 , 62 ] and parasites [ 33 , 34 , 47 , 92 ], bullous pemphigoid [ 59 , 87 , 98 ], intertrigo [ 67 , 74 ...…”
Section: Resultsmentioning
confidence: 99%
“…Table S6 (Supplementary material 5) presents details of included studies regarding review question 2. Most studies ( n = 10) described self-reported skin concerns/complaints or symptoms such as pruritus [ 20 , 34 , 40 , 42 , 45 , 65 , 102 105 ]. Nine studies reported mortality [ 53 , 63 , 64 , 71 , 77 , 79 , 97 , 98 , 106 ] and seven studies dermatology-related medical visits [ 37 , 42 , 43 , 107 – 109 ] or hospital admissions [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 ] Task shifting can be at different levels – general practitioners (GPs),[ 17 18 ] pharmacists, nurses,[ 19 20 ] physician assistants,[ 21 ] and community health workers. [ 12 22 23 ] The value of non-physician health workers in the delivery of care for non-communicable diseases in low- and middle-income countries has been supported by systematic reviews. [ 24 ]…”
Section: Roles Of Community Dermatology In Various Areas Of Healthmentioning
confidence: 99%
“…[ 60 ] Partnership with NGOs foster community-led healthcare initiatives. [ 12 61 ] Various agencies including government and private agencies – as individuals, neighborhood groups, and NGOs– working together in public–private partnerships can sustain public health interventions including community dermatology. The involvement of reputed educational institutions and influential opinion makers such as religious, social, and political leaders are important facilitating factors.…”
Section: Factors Affecting the Effectiveness Of Community Interventio...mentioning
confidence: 99%
See 1 more Smart Citation